The Exemplary of Kiai and the Future Orientation of Santri: A Socio-Cognitive Perspective in the Pesantren Subculture - Wasim, Arif Al; Syukur, Fatah; Wahib, Abdul (Pascasarjana Universitas KH. Abdul Chalim, 2026)
The research is based on the problem of understanding role models in Islamic education which is often treated in a homogeneous and value-neutral manner. This article aims to integrate the concept of prophetic exemplary with social cognitive theory to explain how the observational learning process and modeling of kiai shapes the santri's vision of life. Using a qualitative-conceptual approach with a theoretical-reflective analysis method through a review of literature sources. Conceptually, the kiai’s exemplary grounded in prophetic ethics and actualized in daily interactions, emerges as a transformative model of living that shapes santri’s worldview and conduct, reinforced by the pesantren environment that supports the continuous internalization of values. This modelling directly influences the santri's future orientation in three aspects: spirituality, social responsibility, and life planning. The study concludes that the prophetic exemplary played by the kiai within the pesantren subculture is a form of character development and future orientation formation that is relevant to the needs of contemporary Islamic education. Theoretically, this study extends Bandura's Social Cognitive Theory by contextualizing it within Islamic culture and pesantren subculture. Practically, it suggests the development of character education and collaborative policies to strengthen the formative role of pesantren.